Optimal drying and storage conditions for purple rice based on expected high quality - Nittaya Junka; Chalermchai Wongs_Aree; Chaiwat Rattanamechaiskul (My University, 2017)
The purpose of this research was to study the drying of purple rice (PR) at temperatures of 100 °C, 130 °C, and 150 °C using a fluidization technique in conjunction with storage in packaging consisting of a polypropylene woven bag (PPWB), laminated bag (LB) or laminated bag with an oxygen absorber (LBOA) to protect against a change in the quality of PR during storage for a period of 90 days. Drying at a temperature of 130 °C, other than showing a high drying rate, did not affect the quality in the aspects of the color, the anthocyanin content, the total phenolic content and the antioxidant activity of the PR. The application of such a temperature also made the free fatty acid (FFA) content decrease during the storage period. To maintain the PR at the highest expected quality after drying, it should be stored under LBOA conditions. Practical applications Drying conditions using a fluidization technique and the storage conditions used in the research were selected from the actual functional conditions used at present even though drying at high temperature might adversely result in the degradation of anthocyanins. Contrarily, the conditions selected positively resulted in inactivated lipase enzyme and prevented the hydrolysis lipids in the rice bran from becoming FFAs, which would subsequently give rise to rancidity. In addition, in this research, data comparisons were clearly made on the change in PR quality at various levels of storage conditions. After the tests, the conditions of drying and suitable storage that would attain the expected quality after harvest until the purple rice (PR) reached consumers would be maintained at the maximum quality. The data acquired will be useful and could be applied in the PR production process, which has been increasingly and continuously expanding.
Keywords: Lipid Oxidation; Polypropylene; GABA and Rice Research